2017
DOI: 10.1017/jmech.2017.55
|View full text |Cite
|
Sign up to set email alerts
|

Numerial Study of Vortex-Induced Vibration of Circular Cylinder Adjacent to Plane Boundary Using Direct-Forcing Immersed Boundary Method

Abstract: Vortex-induced vibration (VIV) is an important physical phenomenon as one design a riser or a cylindrical structure in ocean. As the riser or the cylindrical structure is adjacent to a seabed, the boundary effect on VIV is not fully understood yet. The direct-forcing immersed boundary (DFIB) method is used to investigate a two-degree-of-freedom VIV of a flexible supported circular cylinder adjacent to a plane boundary in this study. Furthermore, the effect of the VIV of cylinder on skin friction of the plane b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Chen et al (2019) reported that the cylinder partially submerged in the boundary layer exhibits a prolonged initial branch followed by a lower branch. In contrast to a typical figure-eight orbit of wall-free cylinders, a round oval-shaped motion was observed by Chern et al (2017) They subsequently reported the onset flow velocity for such a mode transition which was increased with decreasing G/D (Li et al, 2013).…”
Section: Introductionmentioning
confidence: 94%
“…Chen et al (2019) reported that the cylinder partially submerged in the boundary layer exhibits a prolonged initial branch followed by a lower branch. In contrast to a typical figure-eight orbit of wall-free cylinders, a round oval-shaped motion was observed by Chern et al (2017) They subsequently reported the onset flow velocity for such a mode transition which was increased with decreasing G/D (Li et al, 2013).…”
Section: Introductionmentioning
confidence: 94%
“…The current numerical method has been effectively applied to a range of problems involving thick rigid structures, such as circular cylinders, airfoils, and spherical solid objects, in past studies. [21][22][23][24][25][26]…”
Section: Two-stage Dfib With Prediction-correction Processmentioning
confidence: 99%
“…The subgrid technique can also be used for solid–fluid boundary interface cells (cut cells) to refine the geometry of the solid body and calculate the fraction efficiently. This type of DFIB approach has been developed and used successfully in many studies 20‐26 . This is also referred to as the one‐stage direct‐forcing IB method.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation